UPAYA PENINGKATAN KETERAMPILAN KERAJINAN TANGAN DALAM MENDORONG PERTUMBUHAN EKONOMI BERKELANJUTAN BAGI IBU RUMAH TANGGA DAN PETANI - Setiawan, Agus; Nurohman, Yulfan Arif; Waluyo, Alif; Ahzar, Fahri Ali; Qurniawati, Rina Sari (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
The agricultural sector has experienced many setbacks that have an impact on the lives of farmers. Unstable income due to planting and waiting for the harvest season is a serious problem for farmers. One of the communities experiencing income constraints from the agricultural sector is the community of Kaliwungu District, Semarang Regency. To solve the income problem, farmers were given training in making handicrafts. The solution to making handicrafts was obtained from the Asset Based Community Development (ABCD) method. The training participants consisted of farmers, female farm laborers, and housewives totaling 50 people. Based on the training carried out, the ability to make handicrafts can be mastered quickly. As a result, training participants were able to innovate in making brooches with special characteristics and in accordance with Muslim clothing without reducing aesthetics. The ability to make handicrafts is an alternative income in the future.